Conselho das cidades: análise da produção decisória de 2004-2017 - Souza, Juliana Morais da Silva (2020)
This dissertation research aims to map the decisions produced by the Council of Cities, in the period from 2004 to 2017, published through its resolutions; classify them according to the Type of Analysis of Decision Patterns - developed by Gurza Lavalle, Voigt and Serafim (2016), updated and adapted by Gurza Lavalle, Guicheney, Vello and Rodrigues (2018); and to verify the existence and variation of decision-making patterns in this participatory institution, exploring explanatory factors (endogenous and exogenous) for the existence and change of such patterns. In the methodology, the case study modality was used, of a descriptive and exploratory character, and the approaches: qualitative, with the use of bibliographic, documentary techniques, and the application of the Decision Analysis Patterns Typology; and quantitative, using statistical techniques to aid data analysis. The analysis turned to the decision-making production of the Council of Cities, in the period from 2004 to 2017, in the sense of exploring what the councils actually do: making decisions (exits), based on the analysis of the resolutions issued by the council. Thus, it was verified in the ConCidades through the mapping carried out the production of 179 resolutions approved in Plenary and published in the Official Gazette in the analyzed period. Through the application of the Decision Standards Typology, it was identified that in the ConCidades there is a predominance of the General Policy Definition (DEF) decisions (53.63% of the decisions produced), this considered the decision standard present in all periods of the council that exist the production of approved and published decisions. In addition, it can be confirmed that there is variation in ConCidades' decision-making production in relation to the number of decisions produced over the years, and that the endogenous and exogenous explanatory factors help to explore the variation in this production. However, in relation to the variation of the decision pattern it is not confirmed in the case of ConCidades, because it was found that the decision pattern of the council (DEF) is constant over the years, and that even with the presence of other types of decisions these are showed in a secondary way if compared to DEF type decisions, in addition to oscillating during the analyzed period.